Nikāḥ Muḥallil as Legal Stratagem: Ethical Challenges in Contemporary Islamic Family Law - Lina Nur Anisa (Faculty of Shariah UIN Ponorogo, 2026)
This study aims to analyze the legal validity and ethical legitimacy of nikāḥ muḥallil in contemporary Islamic law, particularly within the discourse on Islamic family law in Indonesia and Muslim countries. The research focuses on the tension between classical fiqh constructs that allow reconciliation after ṭalāq bā’in kubrā and contemporary critiques of the practice of marriage engineering, which is viewed as a form of ḥīlah and as the manipulation of divorce law. The research employs a normative-doctrinal method with a conceptual approach, maqāṣid al-sharīah, and comparative madhhab analysis. Primary sources include Qur’anic verses, hadith, and classical fiqh literature on divorce and remarriage, while secondary sources consist of contemporary studies on Islamic family law, maqāṣid, and gender justice. Analysis is conducted qualitatively through normative interpretation to assess the alignment between formal fiqh constructs and the substantive objectives of marriage in Islam. The research findings indicate that although nikāḥ muḥallil may be deemed legally valid within certain school frameworks, its ethical legitimacy weakens when the marriage is intentionally performed to facilitate the remarriage of a former spouse. This practice contradicts the maqāṣid objectives of marriage, particularly the protection of dignity, justice, and sincerity of intent. It has the potential to position women as procedural instruments in divorce manipulation. This study contributes to the development of a maqāṣid-based reinterpretation of Islamic family law to reconcile formal legality with ethical integrity in contemporary marriage practices.